2022
DOI: 10.1007/s11042-022-14217-9
|View full text |Cite
|
Sign up to set email alerts
|

The effects of the superstar learning system on learning interest, attitudes, and academic achievements

Abstract: The COVID-19 pandemic has contributed to the production of a mobile learning app-the Superstar Learning System. Designed by Superstar Company, the Superstar Learning System is a mobile application for curriculum learning assisted with PPTs, knowledge dissemination, and management sharing based on micro-service architecture. To identify the effects of the Superstar Learning System, we randomly selected 71 tertiary students to participate in the study. The data were obtained through three research instruments: a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…For a long term, the teaching method of Tourism English in HVC has been focusing on imparting knowledge, like teachers' monologue, while students become the audience, let alone playing roles, so students' experience is not strong. The existing technological teaching tools, such as Superstar learning platform, are not effective enough and are often used only as a tool for grading assignments (Yu, 2022). Teachers also reported that students only passively participated in the learning tasks assigned on the platform and are not motivated to use the existing learning platform to learn actively.…”
Section: Discussionmentioning
confidence: 99%
“…For a long term, the teaching method of Tourism English in HVC has been focusing on imparting knowledge, like teachers' monologue, while students become the audience, let alone playing roles, so students' experience is not strong. The existing technological teaching tools, such as Superstar learning platform, are not effective enough and are often used only as a tool for grading assignments (Yu, 2022). Teachers also reported that students only passively participated in the learning tasks assigned on the platform and are not motivated to use the existing learning platform to learn actively.…”
Section: Discussionmentioning
confidence: 99%
“…This mode enables students and teachers to communicate with one another before, during, and after classes. Establishing a strong bond between educators and students, SSLP can significantly enhance the teaching experience (Yu, 2023).…”
Section: Super Star Learning Platformmentioning
confidence: 99%
“…Future research can also include other mobile applications such as MOOCs (Yu, 2021;Yu et al, 2022c), videos, Rain Classroom (Yu et al, 2023;Yu & Yu, 2021), and Superstar Learning System (Yu, 2022b). Researchers can analyze their utilizations, suggest the ways to address the current challenges these mobile applications brought about and propose a solution for future research and practice.…”
Section: Implications For Future Researchmentioning
confidence: 99%